PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN KOSENTRASI BELAJAR TERHADAP EFEKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS VII SMP N 8 KOTA JAMBI - Sri Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
This study aims to find out about: 1) the effect of the approach Contextual Teaching and Learning (CTL) on the effectiveness of student learning in mathematics class VII SMP N 8 Jambi, 2) the effect of the concentration of study on the effectiveness of student learning in mathematics class VII SMP N 8 city of Jambi, 3) the effect of the approach Contextual Teaching and Learning (CTL) and the concentration of study on the effectiveness of student learning in mathematics class VII SMP N 8 city of Jambi. This research is experimental research with pretest-posttest design Control Group Design.The population in this study were all seventh grade students of SMP Negeri 8 Jambi City 2013/2014 academic year consists of class VIIA, VIIB, VIIC, VIID, VIIE, VIIF, VIIG, VIIH. Sampling using random sampling while the sample drawn is VIID and VIIG class. Data collection tool achievement test shaped in the form of essays, while the test concentrations studied by using a questionnaire (questionnaire).The results of the study are: 1) There is the effect of the CTL approach to effective student learning in mathematics, where before treatment the average results of the experiment class pretest was 39.97 with a standard deviation of 10.01, after a given treatment using CTL approach mean average posttest in the experimental class was 74.13 with a standard deviation of 8.31, 2) there is a concentration effect study of the effectiveness of student learning in mathematics, the higher the concentration the higher learning learning outcomes obtained, and 3) there are significant CTL approach and the concentration of study on the effectiveness of student learning in mathematics because tcount> ttable ie 3.60> 1.67Keywords: CTL approach, Concentration Learning and Effectiveness Study